1999
DOI: 10.1093/ndt/14.10.2433
|View full text |Cite
|
Sign up to set email alerts
|

Improved bacteriological surveillance of haemodialysis fluids: a comparison between Tryptic soy agar and Reasoner's 2A media

Abstract: Microbiological surveillance of haemodialysis fluids, including pre-treated dialysis water samples collected from RO treatment systems, can be performed more precisely with R2A media than TSA, when incubated at 25+/-2 degrees C for 10 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 19 publications
2
53
1
2
Order By: Relevance
“…To demonstrate that FluidFM technology can be used to isolate bacteria, we first used clover leaf washes and randomly selected individual bacteria for subsequent isolation of liquid R2A medium (52). R2A medium was used to cultivate the bacteria, because a wide range of bacteria are able to multiply in this medium and it is commonly used to isolate various bacteria from environmental samples.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate that FluidFM technology can be used to isolate bacteria, we first used clover leaf washes and randomly selected individual bacteria for subsequent isolation of liquid R2A medium (52). R2A medium was used to cultivate the bacteria, because a wide range of bacteria are able to multiply in this medium and it is commonly used to isolate various bacteria from environmental samples.…”
Section: Resultsmentioning
confidence: 99%
“…Employment of a low nutrient substrate such as R2A limits nutrient-shock which may be experienced by stressed cells plated on a nutrient rich substrate and numerous studies have shown that R2A gives superior recovery of CFU in comparison to high nutrient substrates in many different settings (body fluids, water, etc.) (Guerrero, 1987;Horgan, Matheson, McLoughlin-Borlace, & Dart, 1999;Lesne, Berthet, Binard, Rouxel, & Humbert, 2000;Massa, Caruso, Trovatelli, & Tosques, 1998;Reasoner, 2004;Reasoner & Geldreich, 1985;van der Linde, Lim, Rondeel, Antonissen, & de Jong, 1999). A number of studies have successfully utilized R2A to recover bacteria from soils, the lower atmosphere, and extreme atmospheric altitudes (Bodour, Drees, & Maier, 2003;Gentry, Newby, Josephson, & Pepper, 2001;Griffin, 2004;Griffin et al, 2003;Kellogg et al, 2004;Ovreas & Torsvik, 1998).…”
Section: Af548106mentioning
confidence: 99%
“…24 A number of studies report that lower nutrient levels and temperature promote recovery of more bacteria from water samples than are recovered at higher nutrient levels and temperatures. 13,16,19 It has been observed that dialysis fluid does not always yield the same taxa that are recovered from the water used to prepare the fluid, 25,26 that bacteria likely to be pathogenic and those acquired nosocomially are better recovered on high nutrient media at higher temperatures, 17,23 and that "A particular hazard is introduced when the water temperature is raised to 37C within the dialysis machine, since this temperature supports growth of the more dangerous mesotropic bacteria, for example, P. aeruginosa or S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…12 Both approaches have microbiologic rationales: TGEA and R2A methods are performed at a temperature and nutrient level close to that of dialysis water and its resident microorganisms, and have been shown to yield higher colony counts in several studies. 10,[13][14][15][16] TSA-48h cultures are performed at the temperature at which the patient is exposed to dialysis fluid in the dialyzer. 17 In addition, TSA-48h has the operational advantage that results are available more quickly, allowing earlier corrective action, and allows a laboratory to operate more efficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation